The use of adjuvants to improve fungicide spray deposition on grapevine foliage - Van Zyl, Sybrand Abraham (Stellenbosch : Stellenbosch University, 2009)
Thesis (MScAgric (Plant Pathology))--Stellenbosch University, 2009.